A Ten-Year Retrospective Evaluation of 137 Patients with Henoch Schonlein’s Purpura - Osman Dönmez; Nihal Sargın Yıldırım; Oğuzhan Durmaz (Güncel Pediatri)
Introduction: In this study, we have evaluated laboratory, clinical characteristics, and results of Henoch Schonlein’s purpura (HSP) patients diagnosed in Uludag University Hospital Pediatric Nephrology outpatient clinic between 1999 and 2009.Material and Methods: The laboratory, clinical characteristics, and results of the patients were derived from hospital records.Results: Of 137 HSP patients, 48 (35%) were girls, 89 (65%) were boys. Non-thrombocytopenic purpura was present in all patients. Joint involvement was seen in 81 (59.1%) patients. Pulmonary involvement was seen in 4 (2.9%) patients. Gastrointestinal system involvement was seen in 99 (72.3%) patients. Thirty patients underwent a kidney biopsy. In 16 (11.7%) patients grade I, in 2 (1.5%) patients grade 2A, in 3 (2.2%) patients grade 2B, in 3 (2.2%) patients grade 3A, in 5 (3.6%) patients grade 3B, and in 1 (0.7%) patient grade 4 renal involvement was present. When we evaluated the patients according to Meadow’s classification, microscopic hematuria was the most commonly seen finding in 55 (%40.1) patients. Acute nephritic syndrome was present in 15 (10.9%) patients, nephrotic syndrome in 7 (5.19%) patients, familial Mediterranean fever in four 4 (2.9%) patients and poliarteritis nodosa in one (0.7%) patient. On laboratory findings, leukocyte >10000/ml was seen in 60 (43.8%) patients. Seventy two (52.6%) patients were followed without treatment. Other patients were treated with steroids, NSAID and immunosuppressive therapy according to the severity of diseases. In 16 (11.7%) patients recurrence was seen.Conclusion: HSP is a disease that can spontaneously resolve, but sometimes can be present with complications leading to death. Some patients show atypical manifestations. While acutely diagnosed patients should be inspected for complications, the patients should be closely monitored for recurrences and renal involvement after acute period. (Journal of Current Pediatrics 2011; 9: 63-7